Characterisation of brittle structures of bedrock in southern Finland: Unravelling the evolution and properties of fault and fracture systems and their prediction at different scales - Nordbäck, Nicklas (fi=Turun yliopisto|en=University of Turku|, 2024)
The aim of this thesis is to improve the understanding of the brittle tectonic evolution in Fennoscandia, which is known to be complex and contain multiple stages of fault nucleation and reactivation. Building on prior work, this work provides new structural descriptions and temporal constraints of fractures and faults from the Paleoproterozoic bedrock of southwestern Finland. Integration of structural and isotopic data from Olkiluoto, the site of planned nuclear waste disposal, allowed constraining the geometric and temporal relationships of specific sets of brittle faults within the fault network at local scales. However, the Olkiluoto dataset leaves a substantial period of uncertainty in crustal evolution at 1.6-1.3 Ga, and this thesis aims to close this gap through examining novel regional structural datasets from the 1.58 Ga Åland rapakivi batholith for paleostress analysis. Moreover, this work displays the results of multiscale lineaments mapped from southern Finland, providing information on the scalability of brittle structures, localization of regional deformation, and insights into the evolution of the brittle crust under various stress conditions. According to the results of this study, the tectonic development of the brittle crust within southwestern Finland includes at least six major tectonic stages: 1) brittle deformation initiated under NW–SE to NNW–SSE compression at the brittle-ductile transition at around 1.75 Ga. Two successive stages of regional extension followed: 2) N–S extension at around 1.64 Ga during the emplacement of the pre-1.6 Ga rapakivi granites, and 3) E–W to NW–SE extension during the intrusion of the 1.58 Ga Åland rapakivi, diabase dykes, and the onset of the development of a sedimentary basin where the Bothnian Sea is now located. This extensional period was succeeded by strike-slip tectonics including 4) WNW–ESE to NNW–SSE compression between 1.55–1.4 Ga and 5) NE–SW compression at around 1.3–1.2 Ga. 6) NE–SW to ENE–WSW compression during the early phases of the 1.1 Ga Sveconorwegian orogeny resulted in the formation of low-angle faults in Olkiluoto. Any later tectonic events were restricted to reactivations of previously formed faults. The absolute age of the overprinting regional joints remains unknown, but a minimum age of ca. 540 Ma can be inferred from Cambrian sedimentary infillings observed within some of the joints.

---- Tämän opinnäytetyön tavoitteena on kehittää ymmärrystä Fennoskandian kilven hauraasta tektonisesta evoluutiosta, jonka tiedetään olevan sekä monimutkainen että sisältävän useita siirrosten synty- ja reaktivoitumisvaiheita. Tämä työ täydentää aiempia julkaisuja Lounais-Suomen kallioperän rakennekehityksestä uusien rako- ja siirrossystemien karakterisoinnin ja ikämääritysten muodossa. Olkiluotoon sijoitettavan ydinjätteen loppusijoituspaikan kallioperän osalta näiden uuden tulosten keskinäisen integroinnin perusteella kyettiin määrittämään sekä hauraiden siirrosten suhteelliset ikäsuhteet että absoluuttiset iät. Olkiluodon aineisto ei kuitenkaan kata ajallisesti maankuoren evoluutiota mesoproterotsooisen kauden alkuosassa, jonka vuoksi ajanjaksoon 1,6-1,3 Ga liittyy merkittäviä epävarmuuksia. Tällä opinnäytetyöllä pyritään edellä mainitusta syystä täyttämään tätä aukkoa tietämyksessä laatimalla uusiin alueellisiin rakenneaineistoihin perustuvia malleja paleojännityskentästä 1,58 Ga Ahvenanmaan rapakivibatoliitista. Lisäksi tässä työssä esitellään Etelä-Suomesta kartoitettujen monimittakaavaisten lineamenttitukintojen tulokset, jotka antavat tietoa hauraiden rakenteiden skaalautumisesta, alueellisten muodonmuutosten lokalisoitumisesta sekä ymmärrystä hauraan kuoren kehityksestä erilaisissa jännitysolosuhteissa. Tämän tutkimuksen tulosten perusteella maankuoren hauraan tektonisen kehityksen vaiheet Lounais-Suomessa ovat seuraavat: 1) hauras muodonmuutos alkoi NW–SE - NNW–SSE puristuksessa noin 1,75 Ga sitten, kun kallioperä oli jäähtynyt ja hauraiden rakenteiden muodostuminen oli mahdollista. Tätä puristusta seurasi kaksi peräkkäistä ekstensiovaihetta: 2) N–S ekstensio vaikutti yli 1,6 Ga ikäisten rapakivigraniittien asettumiseen ja 3) E–W - NW–SE ekstensio 1,58 Ga Ahvenanmaan rapakiven paikoilleen asettumiseen sekä, diabaasijuonten ja sedimenttialtaan kehitykseen. Näitä vaiheita seurasi kulkusiirrostektoniikka, mukaan lukien 4) WNW–ESE - NW–SSE puristus välillä 1,55–1,4 Ga ja 5) NE–SW puristus noin 1,3–1,2 Ga. 6) 1,1 Ga Svekonorjalaisen orogenian alkuvaiheessa NE–SW - ENE–WSW puristus johti kaateiltaan loiva-asentoisten siirrosten muodostumiseen Olkiluodossa. Kaikki tätä myöhäisemmät tektoniset tapahtumat rajoittuivat jo aiemmin muodostuneiden siirrosten uudelleenaktivoitumiseen. Kallioperästä havaittujen tensiorakojen absoluuttinen ikä on tuntematon, mutta niiden vähimmäisiäksi voidaan päätellä n. 540 Ma perustuen niissä esiintyviin kambrikautisiin sedimenttitäytteisiin.